Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Trần Bảo Hân

Tìm x:

\(4.3^{x+2}-3^{x-1}=963\)

Giúp e với

Nguyễn Đức Trí
30 tháng 7 2023 lúc 9:24

\(4.3^{x+2}-3^{x-1}=963\)

\(\Rightarrow4.3^{x+2}-3^{x+2-3}=963\)

\(\Rightarrow4.3^{x+2}-\dfrac{1}{3^3}3^{x+2}=963\)

\(\Rightarrow4.3^{x+2}-\dfrac{1}{27}3^{x+2}=963\left(1\right)\)

Đặt \(t=3^{x+2}>0\)

\(\left(1\right)\Rightarrow4t-\dfrac{1}{27}t=963\)

\(\Rightarrow t\left(4-\dfrac{1}{27}\right)=963\)

\(\Rightarrow\dfrac{107}{27}.t=9.107\)

\(\Rightarrow t=3^2\Rightarrow t=3^2:\dfrac{1}{3^3}=3^2.\dfrac{3^3}{1}=3^5\)

\(\Rightarrow3^{x+2}=3^5\Rightarrow x+2=5\Rightarrow x=3\)

Trần Đình Thiên
30 tháng 7 2023 lúc 9:24

4\(\cdot\)3x+2-3x-1=963

=>4\(\cdot\)3xx32-3x:3=963

=>3x\(\cdot\)36-3x\(\cdot\)\(\dfrac{1}{3}\)=963

=>3x\(\cdot\)(36-\(\dfrac{1}{3}\))=963

=>3x\(\cdot\)\(\dfrac{107}{3}\)=963

=>3x=963:\(\dfrac{107}{3}\)=27=33

=>x=3


Các câu hỏi tương tự
thịoanhngọchuyền
Xem chi tiết
Nguyễn Tùng Chi
Xem chi tiết
Hạ Thị Thu Hà
Xem chi tiết
Nguyễn Thảo Vy
Xem chi tiết
Xem chi tiết
Selena
Xem chi tiết
Đinh Ngọc Tuệ Nhi
Xem chi tiết
Phạm Thanh Thảo
Xem chi tiết
Tran Thi Nham
Xem chi tiết